A Late Mesoproterozoic 40Ar/39Ar age for a melt breccia from the Keurusselkä impact structure, Finland - Schmieder, M.; Jourdan, Fred; Moilanen, J.; Buchner, E.; Öhman, T. (2016)
Field investigations in the eroded central uplift of the =30 km Keurusselkä impact structure, Finland, revealed a thin, dark melt vein that intersects the autochthonous shatter cone-bearing target rocks near the homestead of Kirkkoranta, close to the center of the impact structure. The petrographic analysis of quartz in this melt breccia and the wall rock granite indicate weak shock metamorphic overprint not exceeding ~8-10 GPa. The mode of occurrence and composition of the melt breccia suggest its formation as some kind of pseudotachylitic breccia. 40Ar/39Ar dating of dark and clast-poor whole-rock chips yielded five concordant Late Mesoproterozoic miniplateau ages and one plateau age of 1151 ± 10 Ma [± 11 Ma] (2s MSWD = 0.11; P = 0.98), considered here as the statistically most robust age for the rock. The new 40Ar/39Ar age is incompatible with ~1.88 Ga Svecofennian tectonism and magmatism in south-central Finland and probably reflects the Keurusselkä impact, followed by impact-induced hydrothermal chloritization of the crater basement. In keeping with the crosscutting relationships in the outcrop and the possible influence of postimpact alteration, the Late Mesoproterozoic 40Ar/39Ar age of ~1150 Ma should be treated as a minimum age for the impact. The new 40Ar/39Ar results are consistent with paleomagnetic results that suggested a similar age for Keurusselkä, which is shown to be one of the oldest impact structures currently known in Europe and worldwide.